Pain Intensity and Misconceptions Among Hospice Patients With Cancer and Their Caregivers: Status After 2 Decades. (May 2017) - Wilkie, Diana J.; Ezenwa, M. O.; Yao, Y.; Gill, A.; Hipp, T.; Shea, R.; Miller, J.; Carrasco, J.; Shuey, D.; Zhao, Z.; Angulo, V.; Suarez, M. L.; et al.
There is little evidence about barriers to pain management or their relationships with pain outcomes of hospice patients with cancer. The purpose of the study was to determine the barriers reported by hospice patients with cancer and their caregivers and the relationships with demographic characteristics and the patients' pain. In this cross-sectional study, we used selected baseline data from an ongoing randomized clinical trial of patient and lay caregiver dyads receiving home-level hospice care. Participants used an Internet-enabled tablet to complete the valid, reliable measures of pain intensity, pain management barriers (Barriers Questionnaire 13 items [BQ-13]), and demographic characteristics. The responses indicate that the 2 areas of highest concern (mean scores >3) to both patients and caregivers were "pain means disease progression" and "constipation." Additionally, 3 other areas of highest concern (mean scores >3) to caregivers were "addiction" pain medicine causing "one to do embarrassing things" and "confusion." The mean BQ-13 scores ranged from 0.2 to 4.9 and averaged 2.6 ± 0.9 for the patients and ranged from 0.5 to 4.7 and averaged 2.7 ± 0.9 for the caregivers. Mean barrier scores remain high and were not different between patients and their caregivers or significantly related to the patients' pain intensity. However, there were differences in race, ethnic, and hospice setting in the barrier scores. Patients with Hispanic heritage reported higher barrier scores than non-Hispanic patients. Together, these findings not only support prior research findings but also contribute new insights about pain intensity and pain barriers that are relevant to hospices serving minorities with cancer.